2023
DOI: 10.3390/nu15040877
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stone Prevention: Is There a Role for Complementary and Alternative Medicine?

Abstract: Complementary and alternative medicine (CAM) is often implemented in kidney stone patients. It consists of preparations including different ingredients, such as herbs, probiotics, and vitamins, often together with alkali, that are classified within the dietary supplementation category. The majority of dietary supplements claiming to treat or prevent kidney stones contain ingredients with conflicting or no scientific evidence to support their claims. Clinicians should advise stone formers that the effects of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Current guidelines recommend maintaining a urine output >2.0–2.5 L/day and a fluid intake of 2.5–3.0 L/day [ 56 ]. Some beverages consumed every day, such as coffee and tea, can also exert a diuretic effect.…”
Section: Risk Factors and Prevention Of Nephrolithiasismentioning
confidence: 99%
See 4 more Smart Citations
“…Current guidelines recommend maintaining a urine output >2.0–2.5 L/day and a fluid intake of 2.5–3.0 L/day [ 56 ]. Some beverages consumed every day, such as coffee and tea, can also exert a diuretic effect.…”
Section: Risk Factors and Prevention Of Nephrolithiasismentioning
confidence: 99%
“…In addition, weight loss in those with obesity or who are overweight is also recommended in order to maintain a normal body mass index (BMI) to reduce the risk of kidney stone formation [ 56 ]. An in vivo study also showed that weight loss through dietary restriction and exercise increases urinary citrate excretion and reduces the risk of kidney stone disease [ 56 ]. In both sexes, physical activity was inversely associated with nephrolithiasis prevalence.…”
Section: Risk Factors and Prevention Of Nephrolithiasismentioning
confidence: 99%
See 3 more Smart Citations